Directive Speech Acts in The Movie “The Message” By Moustapha Akkad - Asmi Yuniati; Sayyidatul Fadhillah; Muhammad Nafi Annury (Vision: Journal for Language and Foreign Language Learning, 2018)
This study is aimed to explain the classifications and to explain the contribution of directive speech acts analysis in the "The Message" by Moustapha Akkad to EFL learner in understanding the expression of giving the command. This study used descriptive qualitative which the writer interprets of utterances that contain the types of directive speech acts in this movie and the contribution of this research in EFL Classroom. The result of the study showed that 213 utterances of the directive of speech acts were successfully identified. There are command (182 data or 85.44 %), order (2 data or 0.94 %), request (10 data or 4.70 %), and suggestion (19 data or 8.92 %). So it can be concluded that the dominant directive is a command because this movie contained many commands of the Prophet Muhammad and his friends in the battle of Badr and Uhud. This result of this research is suggested for students. Teacher as a facilitator can use this movie as learning media. By watching this movie, the student can observe the expression of giving a command. Expression of giving command was found in basic competence (3.4 and 4.4).